Trends in and Perceptions on Urbanisation - Anant, Geetha (Quaestiones Geographicae, 2011)
Escalating mega-city concentrations, perpetuated by investment distortions and rural-urban imbalances in densely populated and economically undeveloped countries, endorse migration, generate pluralities, and create potential conditions for conflict, evoking planners' concern. In a globalising world, national policies tend to comply with international agreements, which do not necessarily synchronise with commitment of welfare states to domestic issues arising from inequities. This is more apparent in economies disadvantaged by large population sizes, sprawling urban agglomerations, preponderance of slums, a large proportion of untrained and illiterate human resources, and differential taxation laws. This paper appraises selected Indian Ocean countries characterised by development imbalances, lop-sided and unmanageable urbanisation on account of limited availability and poor allocation of resources, shift of rural poverty to urban areas, consumption inequities, etc. Most governments have embraced largely aggressive approaches to address this problem, evicting the ‘destitute in-migrants’, or forcibly shifting them. These cannot have a positive and far-reaching impact, and hence incentive-based ‘inclusive’ and ‘participatory’ resettlement strategies are urged.